Plant-based edible vaccines: Can cholera be the case study in Africa? ☆ - (:unkn) unknown (My University, 2025)
Vaccines are employed as a sanitary approach that is implemented to lessen the hurdles caused by infectious diseases on the safety of public health. A vaccine is biologically made from inactive components of microbes, to enhance immunity and as a defense mechanism adverse to parasitic, bacterial and viral illnesses. Nonetheless, the mode of production that involves purification is quite costly, more so, to low and middle-income countries, especially in Africa. Conventional oral cholera vaccines, though commercially available, face logistical challenges to be transported and distributed to target populations such as Africa. Edible vaccines derived from plants, on the other hand, offer cost-effective and bio-friendly production cost, they are easily administered to all age groups and can be grown near-user-site. This article thoroughly assesses the capability of plant-based edible vaccines as an option for immunization against cholera with exclusive concentration on the African continent. ☆ This article is part of a special issue entitled: 'Genetic Engineering in Rare Diseases' published in Journal of Genetic Engineering and Biotechnology.
Keywords: African Research